Retinoblastoma – pattern, presentation and management: a quintessential experience of 5 years - Yalavarthy, Anvesh Karthik; Nandennavar, Manjunath I.; Karpurmath, Shashidhar V. (International Journal of Research in Medical Sciences, 2016)
Background: Retinoblastoma (RB) is the most common intraocular malignancy of childhood. It accounts for 10-15% of cancers that occur in infants. Objective of the study was to determine the pattern, presentation and management of Retinoblastoma (RB) patients at a tertiary cancer care center in South India, during a period of 5 years (1st November 2009 to 1st December 2014). Methods: This study was a retrospective analysis of the medical records of patients diagnosed as having retinoblastoma obtained from hospital information system and our cancer registry. Data sought was demographic characteristics, clinical presentation, investigations done, the methods of management and the treatment outcome of retinoblastoma patients. Results: Total number of cases studied was 31 and total number of eyes studied was 47. Out of 31 cases, 58% were female. 52% had bilateral involvement. The median age at presentation was 24 months. The commonest mode of presentation was leukocoria (55%) followed by proptosis (22%). Out of 47 eyes studied, 87% were advanced tumours belonging to Group D or Group E. Metastasis to the central nervous system was noted in 22.6% patients belonging to either Group D or Group E. Out of the 31 patients, 64.6% patients underwent enucleation. 6 out of 31 cases succumbed to death. Conclusions: Retinoblastoma continues to be a challenge in developing countries. Lack of awareness and inaccessibility to proper healthcare facilities are major stumbling blocks in achieving high cure rates. Educating the public and healthcare professionals, importance of early diagnosis and prompt referral are vital in reducing morbidity and mortality associated with the disease.